Pengaruh Digital Marketing, Electronic Word of Mouth dan Lifestyle terhadap Keputusan Pembelian pada Tiktok Shop Indonesia - Ani, Nurviani (CV. Kalimasada Group, 2023)
This study aims to determine the influence of digital marketing, electronic word of mouth, and lifestyle on purchase decisions in TikTok Shop among students of the University of Technology Sumbawa. This is a quantitative correlational study. The research sample was calculated using Paul Leedy’s formula with total sample found is 100 respondents. The analysis conducted using multiple linear regression, hypothesis testing, t-test, and coeffecient of determination. Based on the results of the analysis, it can be concluded that the variables of Digital Marketing, e-Wom, and Lifestyle significantly influence the Purchase Decisions among students in TikTok Shop Indonesia. The results of the partial t-test show that Digital Marketing (t_calculated = 3.783, t_table = 1.984), e-Wom (t_calculated = 5.353, t_table = 1.984), and Lifestyle (t_calculated = 5.500, t_table = 1.984) partially have a significant influence on Purchasing Decisions. The obtained R-Square value is 0.785 or 78.5%, indicating that approximately 21.5% of the variation in purchase decisions is influenced by other factors not examined in this study